Development of an affinity cryogel for one step purification of lysozyme from chicken egg white - Mól, Paula Chequer Gouveia [UNESP]; Veríssimo, Lizzy Ayra Alcântara; Eller, Monique Renon; Minim, Valéria Paula Rodrigues; Minim, Luis Antonio (Elsevier, 2017)
In this study, a supermacroporous polyacrylamide cryogel was produced by cryo-polymerization and activated with Tris(hydroxymethyl)aminomethane (Tris-cryogel) to be applied as an affinity ligand for a one step purification of lysozyme (LYZ), directly from chicken egg white (EW). The Tris-cryogel presented interconnected pores with size varying in the range of 20–80 μm and swelling capacity of 19.6 ± 0.9 g/g. The axial dispersion of the Tris-cryogel was analyzed at different flow velocities and mobile phase viscosities. It was verified that higher viscosity resulted in a higher degree of dispersion, causing the HETP values to increase from 0.04 cm to 0.8 cm. Adsorption isotherms were measured at 15 °C and 35 °C at pH 7.5. A Langmuir model was fitted to the equilibrium data, with a maximum adsorptive capacity of 285 mg/g at 15 °C and 363 mg/g at 35 °C. Thermodynamic analysis based on the Van't Hoff relationship showed that the process was spontaneous and enthalpically driven. Lysozyme was purified directly from egg white in a one step purification process at different pH values (7.5, 8.5 and 9.5). Independent of the pH, the specificity of Tris-cryogel for lysozyme adsorption was confirmed. At pH 7.5, yield and purification fold were higher (30% and 45). In addition, the effect of the dilution rate on egg white and flow velocity were also analyzed and it was shown that flow velocity did not affected purification and column efficiency, and that diluting the egg white increased yield to 70% with a purification fold of 23. Results show Tris-cryogel is a promising matrix for use in high throughput purification of lysozyme from egg white.
Keywords: Affinity chromatography; Cryogel; Lysozyme; Purification